Cutibacterium acnes: An emerging pathogen in culture negative bacterial prosthetic valve infective endocarditis (IE). (2022) - Patel, Premalkumar M.; Camps, Nicholas S.; Rivera, Cynthia I.; Gomez, Isabel; Tuda, Claudio D.
Abstract: Cutibacterium acnes (previously known as Propionibacterium ) infections are reportedly increasing in patients with implanted foreign material. Though it is a rare cause of bacterial endocarditis, patients with implanted prosthetic valves and devices have potential increased risk. Cutibacterium species are an ubiquitous environmental surface contaminant and typically difficult to culture, in case of high suspicion for infective endocarditis extended duration incubation of blood or any tissue sample and 16S RNA sequencing of any tissue sample is helpful for a microbiological identification. We report a case of a 50 year old male with culture negative prosthetic valve endocarditis in which the pathogen was identified by molecular testing 16S RNA gene sequencing. Highlights: Prosthetic valve endocarditis. Cutibacterium acnes. 16S gene sequencing. Management challange for prostetic valve endocarditis.